Ground beetle (Coleoptera: Carabidae) diversity is higher in narrow hedges composed of a native compared to non‐native trees in a Danish agricultural landscape. Issue 2 (2nd December 2016) - Lövei, Gabor L.; Magura, Tibor
Abstract: Non‐cultivated areas in agricultural landscapes can substantially contribute to biodiversity. Therefore, to examine the role of tree‐line hedges in supporting arthropod diversity in an agricultural landscape, we sampled carabid beetles in three replicates of a native deciduous (hawthorn, Crataegus mono‐gyna ), a non‐native deciduous (rowan, Sorbus intermedia ), and a non‐native coniferous (spruce, Picea spp.) hedge in Jytland, Denmark. We hypothesised that hedgerows with deciduous trees harbour more diverse carabid assemblages than hedges composed of non‐native trees. The number of carabid individuals and species was highest in the hawthorn hedges and significantly lower in rowan and spruce. This was caused by the presence of forest specialist species. Differences in the number of the grassland and the cropland specialist ground beetle individuals and species were not statistically significant among the hedges. Litter depth and the density of herbs and grasses negatively, while hedge width positively influenced carabid diversity. Overall, hedges composed of the native, deciduous hawthorn were superior to ones composed of the non‐native rowan, and especially to coniferous ones to conserve and maintain carabid diversity in this cultivated Danish landscape.